TELEVISÃO, POLÍTICA E HISTÓRIA: DIMENSÕES DA PROBLEMÁTICA SOCIAL NA TELEDRAMATURGIA DE VIANINHA (Revista de História Regional, 2007)
The present article discusses the viewpoint of Vianinha in the television. In setting out for possible articulations between his teledramaturgy and a national project of culture then debated in the multiple layers of the Brazilian society the research in the end reveals the sense attributed by Vianninha to the working in a media vehicle such as the television. Taking as reference the focuses developed in the creation of the television special series like: O Matador, as to analyses the playwright investiture in a particular language that tries to reveal the impasses lived by the popular class and proposes the politicization of everyday life.